Genetic and molecular characterisation of non-tissue culture adapted influenza B viruses detected in Singapore between 2004-2009 - Muhammad Raihan Jumat (2014)
In Singapore, both influenza A and B viruses circulate in significant proportions throughout the year, with bi-annual peaks corresponding to the monsoon seasons. This statistic is not shared in most temperate countries where influenza is only prevalent during winter. Exploiting this unique situation in Singapore, we studied the characteristics of non-tissue culture adapted influenza B clinical specimens collected from SAF servicemen between the years of 2004 and 2009. A total of 81 clinical specimens were received and 66 tested positive for influenza B upon diagnostic PCR. Growth kinetics of these clinical specimens could not be studied as none of these specimens could replicate in tissue culture. Forty-six of these clinical specimens yielded sequence information for further analysis.